The effect of Palm Oil Addition on Whey Protein Edible Film Characteristic (Jurnal Ilmu dan Teknologi Hasil Ternak, 2008)
The aim of this research was to find out palm oil effect on whey protein edible film characteristic. This research used completely randomized design, consisted of three different concentration of palm oil were 5%, 10% and 15% (w/v), each treatment hold on three repetition.The result showed that there was highly significant effect (P<0.01) on wvp (water vapor permeability), protein solubility, and water content. 15% Palm oil addition gave lower value of wvp and protein solubility. Scanning electron microscopy revelaed that palm oil gave uniform microstructure of edible film whey protein. Â  Keywords: edible film whey protein, palm oil, wvp, protein solubility, water content, microstructure